GOVERNMENT BUDGET REVENUES IN AZERBAIJAN: THE TAX BURDEN AND THE ROLE OF THE OIL FACTOR - ASLANOV, Ilkin (CENTRAL ASIA AND THE CAUCASUS, 2015)
This article examines the two main sources of the state budget in Azerbaijan: taxes and oil revenues. In particular, it analyzes variously measured indicators of the tax burden on the Azerbaijan economy compared to other countries in the region and the world, assesses, based on a regression model, the role of the oil factor in generating revenue for the budget, and explores various scenarios for evaluating the sustainability of government budget revenues in the medium term. Based on his assessments, the author shows that steady growth of the non-oil sector by 7%-9% per year is a major condition for maintaining the stability of government revenues in the medium term.